2020
DOI: 10.1504/ijmor.2020.105859
|View full text |Cite
|
Sign up to set email alerts
|

Sion's minimax theorem and Nash equilibrium of symmetric three-players zero-sum game

Abstract: About a symmetric three-players zero-sum game we will show the following results. 1. A modified version of Sion's minimax theorem with the coincidence of the maximin strategy and the minimax strategy are proved by the existence of a symmetric Nash equilibrium. 2. The existence of a symmetric Nash equilibrium is proved by the modified version of Sion's minimax theorem with the coincidence of the maximin strategy and the minimax strategy. Thus, they are equivalent. If a zero-sum game is asymmetric, maximin strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…And also, Nash equilibrium could be used in a three-players Zero sum game. Mr. Satoh and Tanaka showed that without the coincidence of the maximin and minimax strategies, an asymmetric equilibrium in a symmetric three-player zero-sum game might exist [8]. Therefore, for points-based games, we can use zero-sum game theory and Nash equilibria to develop an excellent model for creating a better strategy for one of the parties.…”
Section: Introductionmentioning
confidence: 99%
“…And also, Nash equilibrium could be used in a three-players Zero sum game. Mr. Satoh and Tanaka showed that without the coincidence of the maximin and minimax strategies, an asymmetric equilibrium in a symmetric three-player zero-sum game might exist [8]. Therefore, for points-based games, we can use zero-sum game theory and Nash equilibria to develop an excellent model for creating a better strategy for one of the parties.…”
Section: Introductionmentioning
confidence: 99%
“…Zero-sum game is a concept of game theory, which is a non-cooperative game [1]. It means that the gain of one party must mean the loss of the other party, and the sum of gain and loss of each party is always "zero", and there is no possibility of cooperation between the two parties [2]- [5]. The result of a zero-sum game is that what one side gains is exactly what the other side loses, and the benefit to society as a whole does not increase by a single point.…”
Section: Introduction:research Backgroundmentioning
confidence: 99%